Eicosapentaenoic Acid-Induced Autophagy Attenuates Intervertebral Disc Degeneration by Suppressing Endoplasmic Reticulum Stress, Extracellular Matrix Degradation, and Apoptosis - Lin, Zhen; Ni, Libin; Teng, Cheng; Zhang, Zhao; Wu, Long; Jin, Yu; Lu, Xinlei; Lin, Zhongke (Frontiers in Cell and Developmental Biology, 2021)
Intervertebral disc degeneration (IDD) is a major cause of low back pain (LBP), but there is still a lack of effective therapy. Multiple studies have reported that endoplasmic reticulum (ER) stress and extracellular matrix (ECM) degradation exert an enormous function on the occurrence and development of IDD. Autophagy can effectively repair ER stress and maintain ECM homeostasis. Eicosapentaenoic acid (EPA) can specifically induce autophagy. The purpose of this study is to explore whether EPA can promote autophagy, reduce ECM degradation and ER stress in vitro, thereby reducing cell apoptosis, and to examine the role of protective effects of EPA in an IDD-rat model in vivo. Western blot and immunofluorescence were used to detect the autophagic flux, ER stress, ECM degradation, and apoptosis in nucleus pulposus cells (NPCs) treated by EPA. We also used puncture-induced IDD rats as experimental subjects to observe the therapeutic effect of EPA on IDD. Our findings indicated that EPA can effectively improve the autophagy activity in NPCs, inhibit the endoplasmic reticulum stress process, reduce the degree of cell apoptosis, and exert protective effects on the anabolism and catabolism of ECM. In addition, in vivo investigations demonstrated that EPA ameliorated the progression of puncture-induced IDD in rats. In conclusion, this study revealed the intrinsic mechanisms of EPA's protective role in NPCs and its potential therapeutic significance for the treatment of IDD.